Computer analysis of human behavior - Salah, Albert Ali.; Gevers, Theo.; SpringerLink (Online service). (London Springer London, 2011)
Computer Analysis of Human Behavior presents the key issues and computational tools which will form the foundation of such future applications. With dedicated chapters on both methodology and applications, this essential text/reference provides a broad survey of advanced pattern recognition techniques for the interpretation of complex human behavioral patterns. Clearly structured, the book begins with concise coverage of the major concepts, before introducing the most frequently used techniques and algorithms in detail, and then discussing examples of real applications. Each chapter offers a stand-alone treatment of a relevant topic, covering the most important issues and approaches, as well as predicting future research directions and posing open questions. Topics and features: Contains contributions from an international selection of experts in the field; Presents a thorough introduction to the fundamental topics of human behavior analysis; Investigates methods for activity recognition, including gait and posture analysis, hand gesture analysis, and semantics of human behavior in image sequences; Provides an accessible psychological treatise on social signals for the analysis of social behaviors; Discusses voice and speech analysis for assessing human communicative behavior, combined audiovisual cues, and social interactions and group dynamics; Examines applications in different research fields, from behavioral biometrics and gaming to ambient intelligence for assisted living; Each chapter concludes with review questions, a summary of the topics covered, and a glossary. Ideal for graduate courses on computer analysis of human behavior, this unique text can also be used as a guide for researchers in computer science, cognitive science and psychology. Additionally, professionals and policy-makers working in fields as diverse as ergonomics, biometrics, and healthcare will find this a valuable reference. Dr. Albert Ali Salah is an Assistant Professor at Boğaziçi University, Department of Computer Engineering, Turkey. Dr. Theo Gevers is an Associate Professor at the University of Amsterdam Informatics Institute, The Netherlands, and a Full Professor at the Computer Vision Center in Barcelona, Spain.
Pt. 1. Tools of the trade; pt. 2. Analysis of activities; pt. 3. Social and affective behaviors; pt. 4. Selected applications.
Electronic reproduction.
Keywords: Human activity recognition; Human behavior; Electronic books